PENGEMBANGAN POTENSI LOKAL DAN BUDAYA DESA WALI BEJAGUNG TUBAN MENUJU WISATA RELIGI - Seviyenti Fikroh; Kristin Tri Lestari; Tabitha Sri Hartati Wulandari (PAKEM: Jurnal Pengabdian Kepada Masyarakat, 2026)
Bejagung Village, located in Semanding District, Tuban Regency, has significant potential to be developed as a religious tourism destination. This potential is supported by the existence of the Sunan Bejagung Tomb and various cultural traditions and historical heritage that attract visitors. However, these local resources have not been optimally utilized to promote community empowerment and local economic development. This community service program aimed to develop the local potential and cultural heritage of Bejagung Village by strengthening community capacity to support religious tourism development. The methods employed included observation, focus group discussions, socialization, training, technology implementation, and continuous assistance for the Syech Asy'ari Tourism Awareness Group (Pokdarwis). The technological innovation introduced consisted of training in producing religious tourism souvenir T-shirts using a digital heat press machine, as well as the development of a tourism map to enhance destination promotion. The results indicate an improvement in community knowledge and skills in producing tourism souvenirs, increased participation of the Pokdarwis in destination management, and the availability of promotional media supporting the development of religious tourism in Bejagung Village. This program is expected to strengthen the identity of Bejagung Village as a religious tourism destination while creating sustainable business opportunities and improving community welfare.